Governing the dietary transition: Linking agriculture, nutrition, and health - Paarlberg, Robert L. (International Food Policy Research Institute, 2011)
The best approach to finding positive synergies between agriculture, nutrition, and health may depend on a country's position in the dietary transition—from a diet low in both calories and micronutrients (Stage One) to a diet that provides adequate basic energy for most people but an inadequate balance of nutrients (Stage Two) to an affluent diet that begins to provide excessive calorie energy, which can lead to health problems linked to obesity (Stage Three). As societies move through this dietary transition, the relative importance of government and the most important functions of government will change.